Antidiabetic Activity of Ethanol Extract from Red Spinach Leaves (Amaranthus tricolor L.) on Mice - Salim, Emil; Wulandari, Siti (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
This study aims to determine the antidiabetic activity of ethanol extract of red spinach leaves (Amaranthus tricolor L.) on male mice. The study was conducted experimentally using 25 male mice divided into 5 treatment groups, namely the negative control group (CMC Na 0.5%), positive control (glibenclamide 0,65 mg/kg BW), and 3 others groups given ethanol extract of red spinach leaves at doses of 100, 200 and 400 mg/kg BW. Mice were induced with streptozotocin (STZ) dose of 100 mg/kgbw intraperitoneally. After 72 hours, diabetic mice were treated for 15 days orally and blood glucose levels were checked every 5 days.using a glucotest device. The results showed that Ethanol extract od Red Spinach Leaves (EERSL) doses of 100 and 400 mg/kg BW were not significantly different from the negative control CMC Na (p>0.05) in reducing blood glucose levels. EERSL doses 200 mg/kgbw and positive control glibenclamide significantly reduce blood glucose levels campared to negative control CMC Na (p<0.05). Ethanol extract of red spinach leaves has antidiabetic activity on male mice at a dose of 200 mg/kg BW, whose effect is not significantly different compared to the glibenclamide.